Study of social and demographic determinants of severe acute malnutrition in children aged 6-59 months in a tertiary care centre of Odisha, India - Jena, Pravati; Rath, Soumini; Nayak, Manas Kumar; Satapathy, Diptirekha (International Journal of Contemporary Pediatrics, 2018)
Background: The objective is to study the various social and demographic determinants of severe acute malnutrition in children aged 6 months to 59 months in a tertiary care centre of Odisha, India. Methods: This is a hospital based prospective observational study done in a tertiary care centre of Odisha during the period of Nov 2015 to Oct 2017 in which all children with severe acute malnutrition as per WHO criteria in the age group 6 months to 59 months were enrolled and their socioeconomic and demographic details were evaluated. Results: Present study revealed a prevalence of severe acute malnutrition as 2.8%. Males (54.2%) were more affected than females (45.8%). Most common age group affected was 6-12 months (37.4%). Most of the children were from low socioeconomic status (96.4%) and from rural areas (84.8%).63.7% of the study population were unimmunised. Only 12.6% of the participants were exclusively breast fed.100% of the children in the study population received top feeding with cow’s milk. Conclusions: The prevalence of malnutrition is high in Odisha but most of the causative factors are preventable. Adequate education regarding exclusive breastfeeding, complementary feeding, immunisation, promotion of proper referral and health care services can help to improve nutritional status in the state of Odisha.